The impacts of school on English learners’ motivation in Indonesian Islamic schools - Farid, Achmad; Adara, Reza Anggriyashati; Ashar, Salim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Among the teaching practitioners in Indonesia, there is a general belief that some learners of English in some Indonesian pesantren (Islamic boarding schools) have a negative view on English, which consequently affects their motivation. However, it remains unclear what has affected the trend. The current study investigates this issue in three pesantren schools in Indonesia affiliated with different Islamic groups. Using the L2 Motivational Self System (L2MSS) model proposed by Dörnyei (2009) as an analytical lens, a survey instrument was designed to describe and compare students’ motivation to learn English (n = 376). A multivariate analysis of variance (MANOVA) was run to describe and compare the students’ motivation, and a stepwise multiple regression analysis was performed to discover which motivational factors made the most significant contribution to motivation by predicting reported learning effort in English. In addition, a thorough document analysis was performed to obtain background information regarding the teaching of English in the three institutions. It was found that institutional factors do play a role in influencing the learners’ motivation, in that in the most religiously conservative context, the school policy does shape the learners’ ideal L2 self. As the learners’ ideal L2 self was weak, it leads to weak motivational power as well. The paper concludes by emphasizing the crucial role of educational contexts in shaping students’ ideal selves and in providing favourable learning experience, which are key elements in motivating learners to learn English.